2014
DOI: 10.1016/j.nedt.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reflective writing interventions on the critical thinking skills and dispositions of baccalaureate nursing students

Abstract: The results of this study make it imperative for nursing schools to consider including reflective writing-especially assignments based on Paul's (1993) model-in nursing courses. If future studies, testing over longer periods of time, show significant increases in critical thinking, those interventions could be incorporated into nursing curriculum and change the way nurse educators evaluate students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 13 publications
1
59
1
14
Order By: Relevance
“…Explicit teaching of CT has been studied in-depth by means of instructional models, in which the teacher teaches the theoretical concepts related to the development of CT capacities and skills, in addition to stimulating the development of these skills. Although the only study included in this SR (30) that used an instructional model for teaching CT did not show a significant increase in CT scores, studies have shown the effectiveness of this model in the development of CT abilities and skills in college students (46)(47) . Thus, the authors of the present study encourage research on the effectiveness of the instructional model combined with other teaching strategies, and highlight the need for a theoretical model of CT that better instructs teachers on instruction of CT for undergraduate nursing students.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Explicit teaching of CT has been studied in-depth by means of instructional models, in which the teacher teaches the theoretical concepts related to the development of CT capacities and skills, in addition to stimulating the development of these skills. Although the only study included in this SR (30) that used an instructional model for teaching CT did not show a significant increase in CT scores, studies have shown the effectiveness of this model in the development of CT abilities and skills in college students (46)(47) . Thus, the authors of the present study encourage research on the effectiveness of the instructional model combined with other teaching strategies, and highlight the need for a theoretical model of CT that better instructs teachers on instruction of CT for undergraduate nursing students.…”
Section: Discussionmentioning
confidence: 93%
“…In the remaining 16.7%, the control group's strategy was the same as that used in the intervention group, except for the model that the researcher wanted to test, which were the APA (32) and Role Modeling (35) . It is notable that in only three studies was the intervention proposed based on a conceptual model, such as the 5E Learning Model (29) , Richard Paul's CT Instructional Model (30) and the theoretical model of Role Modeling (35) . It is also notable that in only three studies (14,28,31) was it mentioned that the people who implemented the intervention were trained or had experience with the strategy applied.…”
Section: Days Professional Judgment Rating Form (Pjrf)mentioning
confidence: 99%
“…Over the past decade, a lot of research has investigated the importance of critical thinking dispositions (CTD) (Bell & Loon, 2015;Lewis, 2012;Naber & Wyatt, 2014;Ojewole, 2013;Racchini, 2007;Walter, 2013;Yang, Chuang, Li, & Tseng, 2014). Researchers have reported that CTD are significant because they are a pre-requisite to the development of powerful critical thinking skills (Beyer, 1987;Ojewole, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Spesielt peker hun på å utvikle evnen til å gripe det vanskelige ved virkeligheten, det vil si seg selv og andre i verden. Fra et persepsjonsfenomenologisk perspektiv vektlegger Merleau-Ponty (2012) at kunnskap bygger på subjektet sin direkte eller kroppslig levde erfaring av verden, inkludert ting, andre og seg selv. Gjennom å bevege og uttrykke seg i verden har kroppen, definert som subjekt, en grunnleggende kraft til å gi noe mening.…”
Section: Referee* Innledningunclassified